1986
DOI: 10.1073/pnas.83.22.8774
|View full text |Cite
|
Sign up to set email alerts
|

Structure and replication of the genome of the hepatitis delta virus.

Abstract: The hepatitis 6 virus can be found in the serum and liver of some hepatitis B virus patients. We now report that the RNA genome of serum-derived 6 virus is single-stranded and circular. Livers of infected chimpanzees or woodchucks contained as many as 300,000 copies of genomic strand RNA per average cell, and at least some of this RNA had a circular conformation. Also present in the livers were RNA species complementary to the virion RNA. The genomic RNA was 5-22 times more abundant than this antigenomic stran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
289
1
6

Year Published

1988
1988
2013
2013

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 319 publications
(306 citation statements)
references
References 23 publications
10
289
1
6
Order By: Relevance
“…The small size and circular structure of the HDV singlestranded RNA suggest that it may replicate by a rolling-circle mechanism similar to that proposed for the small plant pathogenic RNAs (viroids and satellite RNAS; Chen et al, 1986;Wang et al, 1986). Both genomic (viral) and antigenomic sequences of RNA are found in HDV-infected cells.…”
Section: Hdv Rna Replicationmentioning
confidence: 90%
“…The small size and circular structure of the HDV singlestranded RNA suggest that it may replicate by a rolling-circle mechanism similar to that proposed for the small plant pathogenic RNAs (viroids and satellite RNAS; Chen et al, 1986;Wang et al, 1986). Both genomic (viral) and antigenomic sequences of RNA are found in HDV-infected cells.…”
Section: Hdv Rna Replicationmentioning
confidence: 90%
“…19 In the first pathway, the RNA undergoes capping and polyadenylation to yield a subgenomic sequence that serves as the mRNA for the sole protein produced from the HDV genome, the delta antigen. [20][21][22] Two variants of the protein are present in vivo, the small and large delta antigens. 23 These two proteins are identical in sequence except at the C-terminus, where Orange and green circles refer to genomic and antigenomic ribozymes, respectively.…”
Section: Hepatitis Delta Virusmentioning
confidence: 99%
“…Together, these results demonstrate that the 62-nt terminal stem-loop segment is sufficient to determine the specificity of template selection+ Although changes in the primary sequence of this segment are tolerated, its specific secondary structure, and in particular positioning of the bulge adjacent to the transcription start site, is critical for efficient template utilization in this in vitro system+ DISCUSSION RNA polymerase II responsible for transcription of mRNA in eukaryotes has also been implicated in RNA synthesis from RNA templates during replication of plant viroids and human HDV+ Based on the presence of multimeric RNAs detected in infected cells, it is generally accepted that both these classes of RNA pathogens replicate by a rolling-circle mechanism (Chen et al+, 1986;Robertson & Branch, 1987)+ Because of the high complexity of this process that involves multimeric, extensively self-complementary RNA sequences of both polarities, detailed studies of the pol II-mediated RNA replication are very difficult+ Here we describe an in vitro system based on HeLa cell NE that supports specific pol II-dependent transcription from HDV RNA templates+ Although a full replication cycle cannot be accomplished under these conditions, this system allows for a detailed analysis of both RNA template and protein factor requirements for HDV RNA-templated transcription+ …”
Section: Sequence Determination At the Template/transcript Junctionmentioning
confidence: 99%
“…The rolling circle mechanism for HDV replication during which multimeric intermediate transcripts are synthesized requires intact circular RNA template for transcription (Branch & Robertson, 1984;Chen et al+, 1986)+ Transcription reaction detected in our in vitro system depends on a specific cleavage of the RNA template, implying that it cannot directly represent the initiation step of HDV RNA replication+ However, initiation of the rolling circle replication involving a similar mechanism is possible by considering a hypothesis of the RNA template switching+ According to this model, pol II would cleave one molecule of HDV RNA and proceed into the elongation phase only after switching to another circular template, using the cleaved template as a primer for initiation of replication+ In fact, the use of primers to initiate replication is a common theme among the viruses+ For example, tRNAs (Gilboa et al+, 1979), capped oligonucleotides cleaved from host mRNAs (Plotch et al+, 1981), or a polypeptide primer (Andino et al+, 1993) are used by reverse transcriptases, influenza, and poliovirus polymerase, respectively+ Utilization of the 39 end of a cleaved HDV RNA molecule as a primer for initiation of HDV replication may represent a similar situation in which RNA structural elements control recognition, specificity of cleavage (initiation) as well as the specificity and efficiency of template switching+ HDV and viroids may share a similar pol II-mediated replication mechanism that requires common sequence/structure elements in the RNA (Branch & Robertson, 1984)+ The template used in this study is derived from the highly conserved, viroid-like region of HDV RNA (Lai, 1995)+ Identification of the Hepatitis Delta Interacting Protein A (DIPA), a human homolog of HDAg, led to the hypothesis that HDV evolved from a viroid-like RNA that acquired HDAg ORF as a result of pol II switching templates from a viroid ancestor to the cellular mRNA (Brazas & Ganem, 1996)+ Furthermore, sequence comparison of a number of viroid variants suggested that RNA template switching may frequently occur during viroid replication (Hammond et al+, 1989;Koltunow & Rezaian, 1989;Rezaian, 1990;Hernandez et al+, 1992;Kofalvi et al+, 1997)+ Notably, stem-loops present at both ends of viroid RNAs are directly implicated in template switching during viroid replication (Semancik et al+, 1994;Diener, 1995)+ Further studies are necessary to determine if a similar template switching may also occur during HDV RNA replication+ Alternatively, it is possible that in contrast to the initiation of HDV transcription observed in vitro, initiation of HDV replication in vivo proceeds by a mechanism that does not require RNA cleavage, but still depends on a specific recognition of the same AG HDV RNA element for de novo initiation by pol II+ In that case, the observed template cleavage could reflect suboptimal conditions of the in vitro reac...…”
Section: Implications For Hdv Rna Replication In Vivomentioning
confidence: 99%